Effects of Weizhuan’an on rats with precancerous lesions of gastric cancer based on regulating gastric mucosal microflora and inflammatory factors - Lu, Yuting; Liu, Huayi; Shang, Jiaju; Mao, Yijia; Meng, Lingkai; Gao, Changbai (Frontiers in Pharmacology, 2024)
Observe the intervention of Weizhuan'an Prescription on rats with precancerous lesion of gastric cancer (PLGC) as well as its regulation on gastric mucosal microflora and inflammatory factors, and to explore the pharmacodynamic mechanism of Weizhuan'an Formula. The rats were divided into blank control group (BCG), low, medium and high dose groups of Weizhuan'an Prescription (LDG, MDG, HDG), and natural recovery group (NRG) at random. The rats in traditional Chinese medicine (TCM) were given corresponding doses of Weizhuan'an Formula, while the rats in NRG and BCG with the equivalent distilled water for 12 weeks. After that, gastric mucosa samples of rats were collected to observe the general and pathological changes of gastric mucosa, the changes of gastric mucosal microflora were detected by 16S rDNA amplicon sequencing, and the inflammatory factors were analyzed by cytokine antibody microarray and western blotting. The results suggest that compared with the BCG, the pathology of gastric mucosa and gastric mucosal microflora and inflammatory factors in rats with PLGC have changed significantly, while Weizhuan'an Formula effectively improved them, especially the MDG and HDG (P<0.05). Compared with the NRG, the abundance of probiotics such as Lactobacillus and Veillonella were increased, while the pathogens such as Proteobacteria and Pseudomonas were decreased (P＜0.05, P＜0.01), the relative contents of IL-2, IL-4, IL-13 and MCP-1 in gastric mucosa were decreased (P＜0.05). Moreover, it can up regulate the DNA-binding transcriptional regulator, ABC-type multidrug transport system, and related enzymes, and affect the signal pathways such as Viral protein interaction with cytokine and cytokine receptor, T cell receptor signaling pathway significantly (P＜0.05, P＜0.01), which can promote drug absorption and utilization and repair damaged gastric mucosa. The study confirmed that Weizhuan'an Prescription can treat rats with PLGC by regulating gastric mucosal microflora and inflammatory factors.